2018
DOI: 10.3847/1538-4365/aab9b4
|View full text |Cite
|
Sign up to set email alerts
|

X-UDS: The Chandra Legacy Survey of the UKIDSS Ultra Deep Survey Field

Abstract: We present the X-UDS survey, a set of wide and deep Chandra observations of the Subaru-XMM Deep/UKIDSS Ultra Deep Survey (SXDS/UDS) field. The survey consists of 25 observations that cover a total area of 0.33 deg 2 . The observations are combined to provide a nominal depth of ∼600 ksec in the central 100 arcmin 2 region of the field that has been imaged with Hubble/WFC3 by the CANDELS survey and ∼200 ksec in the remainder of the field. In this paper, we outline the survey's scientific goals, describe our obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 75 publications
3
79
0
Order By: Relevance
“…Also, we remind that the lower number of associations found in this work as compared to that of Kocevski et al (2018) derives from the fact that we only looked for counterparts within VANDELS, without enlarging our search to all catalogues available in the literature. At variance with §3.1, we could not check for how many of the counterparts provided by Kocevski et al (2018) coincide with those found in the present work, since the Kocevski et al (2018) catalogues only include redshift information without listing their coordinates. Figure 4 illustrates the distribution of unobscured X-ray luminosities for all the Kocevski et al (2018) sources with a VANDELS identification.…”
Section: Udsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, we remind that the lower number of associations found in this work as compared to that of Kocevski et al (2018) derives from the fact that we only looked for counterparts within VANDELS, without enlarging our search to all catalogues available in the literature. At variance with §3.1, we could not check for how many of the counterparts provided by Kocevski et al (2018) coincide with those found in the present work, since the Kocevski et al (2018) catalogues only include redshift information without listing their coordinates. Figure 4 illustrates the distribution of unobscured X-ray luminosities for all the Kocevski et al (2018) sources with a VANDELS identification.…”
Section: Udsmentioning
confidence: 99%
“…Relatively deep X-ray observations of the UDS field are presented by the recent work of Kocevski et al (2018) who provide a catalogue of 864 sources observed down to a depth of ∼ 600 Ks in the central 100 arcmin 2 and to ∼ 200 Ks in the remainder of the field. As it is possible to appreciate from Table 4, of these 864 sources 628 fall within the VAN-DELS area, 414 have a VANDELS counterpart obtained as in §3.1, and 97 also possess a spectroscopic redshift determination.…”
Section: Udsmentioning
confidence: 99%
See 2 more Smart Citations
“…C.-C. Chen et al: Extended Hα over compact far-infrared continuum in dusty submillimeter galaxies (a) The AGN classification in X-ray is based on catalog matching; ALESS SMGs are matched to the Chandra 7 Ms catalog and classified as AGN based on the criteria set in Luo et al (2017). The AS2UDS SMGs are matched to the Chandra X-UDS catalog (Kocevski et al 2018) with a simple luminosity cut of L 2−10kev > 3 × 10 42 erg s −1 , which is one of the criteria used in Luo et al (2017). The steep slope in mid-infrared has suggested that ALESS75.1 is an IR AGN Stanley et al 2018 (Table 1) with a size of 25×25 kpc and a color stretch from zero to 99.5% of the peak.…”
Section: Introductionmentioning
confidence: 99%